MANAJEMEN MATA RANTAI BISNIS SEBAGAI PELUANG PENINGKATAN PRODUKTIVITAS PERUSAHAAN - Nurdin Brasit (AkMen JURNAL ILMIAH, 2011)
To be able to uncover opportunities for the company's overall productivity (Total Productivity Improvement), it is necessary to first understand how a business achieve its goals through linkage demands in managing every business chain, therefore, need to think about efforts to consolidate efforts and strategies into the company. Consolidation is needed to better ensure that each component involved in the entire chain of business activities are managed in a productive, thus increasing company productivity. This paper attempts to outline the management chain as a chance to increase the productivity of business firms by analyzing the ultimate goal of managing a business that is achieving customer satisfaction as the last matarantai of business activities, by meeting the demands. Customer demands are grouped into five aspects which include Quality, Cost, Delivery time, Safety, and Morale. To be able to meet customer tutntutan yag poured through his mind or feelings, then as a manufacturer of products / services should be able to translate the desire is still abstract into more concrete form or real form of product designs or packages of services to be produced..